Optical techniques for remote and in-situ characterization of particles pertinent to GEOTRACES. (April 2015) - Boss, Emmanuel; Guidi, Lionel; Richardson, Mary Jo; Stemmann, Lars; Gardner, Wilford; Bishop, James K.B.; Anderson, Robert F.; Sherrell, Robert M.
Highlights: We survey the literature of optical measurements of oceanic particles. We relate the measurements to the physical and biogeochemical properties of particles. We examine methods of particular interest for open ocean work. We focus on commercially available sensor technology. We provide specific recommendations for GEOTRACES related work. Abstract: Field and laboratory characterization of marine particles is laborious and expensive. Proxies of particle properties have been developed that allow researchers to obtain high frequency distributions of such properties in space or time. We focus on optical techniques used to characterize marine particles in-situ, with a focus on GEOTRACES-relevant properties, such as bulk properties including particle mass, cross-sectional area, particle size distribution, particle shape information, and also single particle optical properties, such as individual particle type and size. We also address the use of optical properties of particles to infer particulate organic or inorganic carbon. In addition to optical sensors we review advances in imaging technology and its use to study marine particles in situ. This review addresses commercially available technology and techniques that can be used as a proxy for particle properties and the associated uncertainties with particular focus to open ocean environments, the focus of GEOTRACES.